Higher Education Sector and Public Policy : Analysis of Obstacles and Challenges in The Prabowo Era - Pratiwi, Checilia Indah Hari; Gunawan, Cakti Indra (IRDH International Journal of Social Sciences & Humanities, 2024)
The purpose of this paper is to explain public policy in the higher education sector. This research method uses descriptive analysis with literacy comparisons and triangulation methods. The results of this study indicate that public policy in the higher education sector plays an important role in determining the direction, quality and equitable access to education. Literacy analysis and triangulation of higher education policies in various countries have similarities in terms of improving quality, relevance to the needs of the world of work, and equitable access, but there are differences in financing approaches and governance models. Overall, effective public policies in the field of higher education must pay attention to quality access, inclusiveness, and sustainability to answer the challenges of globalization and technological development.